Limited adoption of short rotation coppice: The role of farmers' socio-cultural identity in influencing practice. (June 2016) - Warren, Charles R.; Burton, Rob; Buchanan, Olivia; Birnie, Richard V.
Abstract: UK energy policy promotes biomass energy crops as potentially significant contributors to renewable energy targets, but few farmers have planted these crops. Amongst the many possible explanations for this disconnect between policy ambitions and delivery on the ground, the role of farmers' socio-cultural identity has received little attention. This study focuses on the Lockerbie area in south-west Scotland, a potentially favourable location for perennial energy crops because (i) it is biophysically suitable for short rotation coppice (SRC) willow, and (ii) Britain's first wood-fueled power station provides a significant local market. A survey in 2009 explored farmers' perceptions of SRC willow, and the key reasons why they adopt or reject perennial energy crops. The results show that most farmers regard SRC willow as a financially risky, overly committing and inappropriate crop for their farms. Whilst financial factors are influential, even large potential profits would be insufficient to persuade many farmers to adopt SRC. Non-financial factors related to identity, lifestyle, farming culture and the perceived priority of food production powerfully shape the overwhelmingly negative attitudes of farmers to SRC. These findings suggest that biomass energy policy, especially regarding woody crops like SRC willow, needs to be more precisely tailored to influential social factors such as socio-cultural identity and local producer culture. Highlights: Most farmers reject policies promoting the establishment of perennial energy crops. Cultural factors strongly influence farmers' negative perceptions of energy crops. Ignoring farmers' values and motivations compromises effective policy delivery. Identifying land for energy crops is theoretically easy but practically challenging.